Women’s Resistance toward Patriarchy Domination in Novel The Vegetarian (2015) by Hankang - Nahdatul Nisaq; Muhd. Al- Hafizh (English Language and Literature, 2022)
This thesis is an anlysis of a novel written by Hankang entitled The Vegetarian (2015). The problem of this analysis focuses onthe issue of women’s resistance toward patriarchy domination. This analisys deal with transformative ecofeminism theory. This study aims to find the forms of patriarchy domination toward women and to investigate women’s resistance toward patriarchy domination.